EMPAT CARA UNTUK MENENTUKAN NILAI INTEGRAL POISSON - Novrialman '; Sri Gemawati; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Poisson Integral is one of the definite integrals that can not be solved by an elementary technique. In this article, we discuss four ways to solve the Poisson integral on the interval [-1, 1], that is using the Riemann sum, functional equations, parametric derivatives and infinite series. All of the methods produce the same solution.